Gene expression of estrogen and oxytocin receptors in the uterus of pregnant and parturient bitches - Veiga,G.A.L. (2015)
In the canine species, the precise mechanisms of pregnancy maintenance and the initiation of parturition are not completely understood. The expression of genes encoding the receptors for estrogen (ERα mRNA) and oxytocin (OTR mRNA) was studied in the endometrium and myometrium during pregnancy and parturition in dogs. Real-time PCR was performed to quantify the levels of ERα mRNA and OTR mRNA in the uterus of bitches during early (up to 20 days of gestation), mid (20 to 40 days) and late pregnancy (41 to 60 days), and parturition (first stage of labor). All tissues expressed ERα and OTR mRNA, and are thus possibly able to respond to eventual estrogen and oxytocin hormonal stimuli. No statistically significant differences in the expression of ERα mRNA were verified in the endometrium and myometrium throughout pregnancy and parturition, but expression of OTR mRNA increased at both parturition and late pregnancy. We concluded that the increase of endometrial and myometrial OTR mRNA expression in dogs is not an event dependent on estrogenic stimulation. Moreover, the contractility response of the canine uterus to oxytocin begins during pregnancy and maintains myometrial activity. The expression of OTR mRNA in canine uterine tissues varied over time, which supports an interpretation that the sensitivity and response to hormone therapy varies during the course of pregnancy and labor. Further studies are needed to elucidate the factors underlying the synthesis of uterine oxytocin receptors and the possible role of ERβ rather than ERα in the uterine tissues during pregnancy and parturition in dogs.